PENGARUH SUHU DAN pH TERHADAP HIDROLISIS CMC OLEH ENZIM SELULASE DARI ISOLAT BAKTERI LARVA KUPU-KUPU COSSUS COSSUS - Maswati Baharuddin; Abd. Rauf Patong; Ahyar Ahmad; Nursiah La Nafie (Teknosains, 2014)
Cellulase enzymes can be isolated from microorganisms that are resistant to high pH and temperature. Cellulase enzyme has a different character depending on the source and the enzyme environment. This study aimed to characterize the cellulase enzymes from bacteria isolates CC2 dan CC4 which includes the determination of the optimum pH and temperature of the enzyme activity. In this study, an enzyme produced from isolates of bacteria larva Cossus cossus by centrifugation cold 4 ° C with a speed of 3000 rpm for 15 min to obtain a crude extract of the enzyme cellulase. Determination of pH performed using sitrat acid buffer(3; 3,6; 4; 4,6; 5;5, dan 5) and phosphate buffer with pH variation (6,0; 6,5; 7,0; 7,5; dan 8,0), while for the determination of done an optimum temperature variations in temperature (20, 30, 40, 50, 60, 70, 80, dan 90) ° C enzyme activity were further tested using the Nelson-Samogy measured on a UV-Vis spekrofotometer at a wavelength of 545 nm. Result showed greatest activity isolat CC2 at pH 7,5 enzyme cellulase activity of 15,8806 x 10-4 U / mL while the optimum temperature of 70 ° C with the activity obtained at 19,4121 x 10-4 U / mL. Greatest activity isolat CC4 at pH 4 enzyme cellulase activity of 15,4069 x 10-4 U / mL while the optimum temperature of 70 ° C with the activity obtained at 20,3487 x 10-4 U / mL